Formulation of hetero-aggregates in opposed jet fluidized beds - Favaro Nascimento, Raul; Men, Jialin; Düsenberg, Björn; Schmidt, Jochen; Bück, Andreas (Powder Technology, 2025)
Nanoparticle powders produced by mixing have applications in catalysis, coatings, and advanced materials, yet they remain challenging owing to the strong cohesive behavior of the constituents. Hetero-aggregates form through hetero-contacts at interfaces between chemically distinct materials, but achieving a uniform distribution of components requires an efficient mixing process. Opposed jet fluidized beds offer a promising approach for overcoming these limitations. In this study, the formulation of titania-zirconia hetero-aggregates was investigated by analyzing process parameters and their impact on the inter- and intra-aggregate mixing quality. The effects of feed composition mass ratios (1:1, 2:1, and 1:2), back pressures of the Laval nozzles (0.5, 2.5, and 5.0 bar), and processing times (1 and 5 min) were evaluated by mapping the Ti atomic fraction. The composition and shape of the hetero-aggregates were investigated. The hetero-aggregates exhibited compositions closely aligned with the expected values, based on the initial masses of the components. Shape analysis revealed star-like, elongated, and irregular structures, with circularity and roundness values of approximately 0.4 and 0.5, respectively. Most hetero-aggregates exhibited porosities between 0.971 and 0.991, indicating highly porous structures with significant void spaces. These findings demonstrate that opposed jet fluidized beds enable control over the composition and morphology of hetero-aggregates, leading to efficient nanoparticle mixing.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aggregation; Fluidization; Mixing; Nanoparticles